2014
DOI: 10.3109/08039488.2014.929741
|View full text |Cite
|
Sign up to set email alerts
|

Well-being and depression in individuals with subclinical hypothyroidism and thyroid autoimmunity—A general population study

Abstract: Elevated anti-TPO levels cannot be used as a general marker of poor well-being or depression in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
1
25
0
7
Order By: Relevance
“…In another study, Medici et al found an association between low-normal TSH within the reference range and risk of developing depression independently of gender, and confirmed in prospective analysis (Medici et al, 2014). But other studies found no association between thyroid dysfunction and depression (Beydoun et al, 2013; Engum et al, 2005; Fjaellegaard et al 2015; Saltevo et al, 2015; van de Ven et al, 2012). The methodological approaches, the test used to assess the depression, and the different sample size used in the various studies might partly justify the contrasting results.…”
Section: Discussionmentioning
confidence: 82%
“…In another study, Medici et al found an association between low-normal TSH within the reference range and risk of developing depression independently of gender, and confirmed in prospective analysis (Medici et al, 2014). But other studies found no association between thyroid dysfunction and depression (Beydoun et al, 2013; Engum et al, 2005; Fjaellegaard et al 2015; Saltevo et al, 2015; van de Ven et al, 2012). The methodological approaches, the test used to assess the depression, and the different sample size used in the various studies might partly justify the contrasting results.…”
Section: Discussionmentioning
confidence: 82%
“…In some studies, patients with thyroid failure and euthyroid patients with Hashimoto's thyroiditis seemed to be more prone to the development of depression. However, other authors observed no association between mild hypothyroidism and the presence of depression and found that in the general population, positive antibodies against thyroid peroxidase (TPOAb) cannot be used as a general marker of poor well‐being or depression …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Thyroid peroxidase antibodies (TPO) have been linked to depressive states. Depression is variable and is prejudiced by vulnerability and the gradation, though not always, of thyroid catastrophe [3].…”
Section: Resultsmentioning
confidence: 99%
“…All of the three studies have a small sample size and have high chances of selection bias. A large sample size, unselected cohorts with thyroid antibody assessment are essential for the resolution of this issue [3,11].…”
Section: Autoimmunitymentioning
confidence: 99%